Analysis of Natural Dye Batik Waste Management in Ciwaringin Village that is Integrated into Science Learning in Elementary Schools as an SDGs Program - Margareth, Niniss; Tresnawati, Nailah; Permana Putri, Dian (JTP - Jurnal Teknologi Pendidikan, 2024)
Batik is a cultural heritage of Indonesia, this is recognized by UNESCO that batik is an Indonesian culture that must be preserved. But in reality, the development of the batik industry is inversely proportional, Impact on the environment where the batik industry uses a lot of synthetic dyes, which have a negative impact on the surrounding aquatic environment. The purpose of this research is to analyze the process of processing batik waste using natural dyes carried out by batik craftsmen in Ciwaringin village then the natural dye process can be integrated in science learning in elementary schools as one of the SDGs programs that utilize local potential and improve environmental conservation in the surrounding environment so that the waste produced does not damage the environment. The research method used is descriptive qualitative method, where data collection uses interviews, observation and documentation. Data analysis was carried out with three main stages, namely data collection through exploration, data reduction, analysis, and integration in science learning in elementary schools. The results showed that the analysis of waste treatment starting from the process of making natural dyes, the process of making batik and the results of coloring the resulting waste is very low in residual waste so that batik products using natural dyes can be analyzed in terms of local wisdom that can be integrated in science learning in elementary schools, this can be used as an SDGs program in elementary schools that has a positive impact on the environment. The implication of this research is an effort to implement education to create local wisdom and environmental preservation and stimulate student creativity in creating art products that have SDGs sustainability values.